Control of lipid oxidation with antioxidants during frozen pork shelf-life - Stayner, Rebecca Marie (Kansas State University, 2023)
Antioxidants are used to limit oxidation in many food products; however, there is limited published research evaluating the incorporation of antioxidants in ground pork trim. The objective of this research was to assess lipid oxidation in ground pork fat trim containing no antioxidants, nitrite at 70 ppm, citric acid-based vinegar buffered to 6.0 to 7.0 pH at 0.35% of the total formula, rosemary extract at 0.3% of the total formula, and rosemary green tea (RGT) extract at 0.28% of the total formula during 12 m of frozen storage at -17°C. The treatments (nine replications) were packaged in plastic, heat-sealed bags that were cased in a corrugate box with a weight of 22.68 kg. Treatments, quick frozen at a wind chill of -42°C, reached an equilibrated temperature of -28°C within 26 h and were stored in a commercial freezer at -17°C. Fatty acid profiles and proximate analyses were analyzed for each treatment at the beginning of the study. The control and vinegar treatments at 61.65 and 61.15% fat, respectively, had higher (P < 0.01) percent fat than the nitrite, RGT, and rosemary treatments and was higher than the 58 ± 2% target. This, however, was attributed to a small sample size from a larger batch that was evaluated in real time on the production line to be within 2% of 58%. There were slight differences (P < 0.05) in fatty acid profiles and proximate analyses among the treatments, and these differences were potentially due to sample collection in a commercial pork processing facility where hogs were sourced from multiple production facilities. The aerobic plate count and pH of the samples were measured each month for 12 m. The aerobic plate counts ranged from 2.47 to 2.98 log₁₀ CFU/g throughout 12 m storage at -17°C and 2.69 to 2.80 log₁₀ CFU/g among the individual treatments. Pork trim pH varied from 5.79 to 6.23 during 12 m of storage. The nitrite treatment had a higher (P < 0.05) pH than the pork trim containing rosemary. Lipid oxidation was measured monthly using thiobarbituric acid reactive substances (TBA), gas chromatography, and a trained sensory panel. The malonaldehyde (MDA) of RGT and rosemary treatments remained below 0.2 mg MDA/kg during frozen storage. The control, vinegar, and nitrite treatments, however, increased resulting in higher (P < 0.05) MDA at 8 through 12 m than rosemary and RGT. Vinegar exceeded 1.0 mg MDA/kg at 12 m, where a consumer is likely to taste oxidation in a pork product. Hexanal, measured by gas chromatography, was similar (P < 0.05) for the control, rosemary, and RGT treatments during storage and stayed at or below 0.1 mg hexanal/kg throughout the 12 m of frozen storage. None of the treatments, however, exceeded 1.0 mg hexanal/kg, or reached levels of hexanal that would impact sensory. The trained sensory panel ranked rancid aroma, cardboard aroma, rancid flavor, and cardboard flavor on a 100-point scale where 0 was none and 100 was intense aroma or flavor. All treatments for all four measurements were below 7 on the 100-point scale at each month through 10 m. At 11 m, the vinegar treatment was removed from further evaluation due to due to off aroma and flavors such as meat or sour, though not defined as oxidation. The largest sensory differences among the treatments occurred at 12 m of storage where rosemary and RGT were lower (P < 0.05) than control for rancid and cardboard aroma and flavor. None of the treatments exceeded 30 on the sensory scale. The color was measured instrumentally and by the trained sensory panel using the National Pork Board 6-point scale. The reaction of nitrite with myoglobin impacted the color of the trim based on lower (P < 0.05) a* and b*; however, this color change is expected in a cured product. All the color differences were less than 3 on the color scale, and most were below two. Since most of those differences only a trained panelist will notice, the instrumental color changes do not eliminate any of the treatments. As a result, Rosemary and RGT treatments were effective at slowing oxidation of frozen pork trim during 12 m of storage and may be used to create a flexible supply chain. to maintain pork quality during frozen storage.
Keywords: Frozen pork; Lipid oxidation; Antioxidant; Pork fat